ANALISIS LITERASI KEUANGAN DAN DUTA PASAR MODAL BURSA EFEK INDONESIA BAGI MAHASISWA/I UNIVERSITAS MUHAMMADYAH PONTIANAK DAN UNIVERSITAS WIDYA DHARMA PONTIANAK KALBAR - Regita Ariani; Jones Parlindungan Nadapdap (Jurnal Pengabdian Bukit Pengharapan, 2023)
The results of the opening of the Capital Market Ambassador account for Students of Widya Dharma University Pontianak and Pontianak Muhammadiyah University as the Best Investment Gallery in West Kalimantan. This activity aims to increase capital market literacy and inclusion, by ensuring that the public disseminates information about the world of investment in the capital market. This research was conducted in Pontianak with the IDX representative for West Kalimantan on March 30 2023 and the main objects in this assistance were students Widya Dharma University Pontianak and Muhammadiyah Pontianak University as the Best Investment Gallery in West Kalimantan. The data sources used in this study are based on primary data, which is data obtained directly from direct observation of the process of opening a Capital Market Ambassador account as a result of observations from the informant, namely Mrs. Nor Aeni, to obtain information as well as other supporting data related to this research obtained from study reports or studies and various other literature sources